H-NMR Spectroscopy Analysis of Homo- and Copolymers of L-lactic Acid (Journal of Fiber Bioengineering and Informatics, 2009)
A direct polymerization process was developed to synthesize homo- and copolymers of L-lacticacid. The properties and structures of the products were characterized by ¹H nuclear magnetic resonance(¹H-NMR). It was found that PLLA can be prepared by direct synthesis using melt polycondensation.Moreover, the number-average molecular weight (\overline{Mn}) and compositions of each polymer was determinedby ¹H-NMR spectra. In the meantime, the ¹H-NMR spectra was also used for racemization analysis..
Keywords: Poly(lactic acid); ¹H nuclear magnetic resonance; number-average molecular weight; racemization